Nomogram for predicting lymph node metastasis rate of submucosal gastric cancer by analyzing clinicopathological characteristics associated with lymph node metastasis - Zheng, Zhixue; Zhang, Yinan; Zhang, Lianhai; Li, Ziyu; Wu, Aiwen; Wu, Xiaojiang; Liu, Yiqiang; Bu, Zhaode; Ji, Jiafu (Chinese Journal of Cancer Research; Vol 27, No 6 (December 22, 2015): Chinese Journal of Cancer Research, 2015)
Background: To combine clinicopathological characteristics associated with lymph node metastasis for submucosal gastric cancer into a nomogram. Methods: We retrospectively analyzed 262 patients with submucosal gastric cancer who underwent D2 gastrectomy between 1996 and 2012. The relationship between lymph node metastasis and clinicopathological features was statistically analyzed. With multivariate logistic regression analysis, we made a nomogram to predict the possibility of lymph node metastasis. Receiver operating characteristic (ROC) analysis was also performed to assess the predictive value of the model. Discrimination and calibration were performed using internal validation. Results: A total number of 48 (18.3%) patients with submucosal gastric cancer have pathologically lymph node metastasis. For submucosal gastric carcinoma, lymph node metastasis was associated with age, tumor location, macroscopic type, size, differentiation, histology, the existence of ulcer and lymphovascular invasion in univariate analysis (all P